MATLAB control systems engineering - Pérez López, César (Apress, 2014)
MATLAB is a high-level language and environment for numerical computation, visualization, and programming. Using MATLAB, you can analyze data, develop algorithms, and create models and applications. The language, tools, and built-in math functions enable you to explore multiple approaches and reach a solution faster than with spreadsheets or traditional programming languages, such as C/C++ or Java. MATLAB Control Systems Engineering introduces you to MATLAB and its Control System Toolbox, with practical hands-on examples so that you?ll learn how to create control systems in MATLAB, from models of linear invariant systems, time as transfer functions, zero/pole/amplification or form of State space. You?ll see how you can manipulate both discrete and continuous time systems, and make conversions between various representations of models. Once you?ve mastered the MATLAB Control System Toolbox, you?ll also be able to calculate and graph time response, frequency response, and loci of roots. Plus how to perform placement of Poles, optimal control, and estimates.
Keywords: MATLAB.; MATLAB; Control theory -- Computer programs.; Computer-aided engineering.; elektronické knihy; electronic books